Impact of digitalization on clean governance: An analysis of China’s experience of 31 provinces from 2019 to 2021 - Xiaoyan, Du; Ali, Majid; Le, Xu; Qian, Wu; Xuelian, Gao (Frontiers in Psychology, 2022)
Establishing a corruption-free in other words clean government is an important goal of deepening reforms of the government institutions of China. Open data (OD) is a step toward clean government (CG). It is an important indicator to measure CG through the revolution of information of provincial governments. Analyzing the specific impact of the OD at the provincial level may have clean effects and may bring new ideas for the building of a clean government in the Digital age of China. To test these hypotheses 31 provincial governments are clustered as middle, high, and low open data holders (ODH) and their impact on clean governance from 2019 to 2021 has been analyzed by fsQCA 3.0 software. To know the impact of digitalization of information in provincial governments the Technology Organization Environment (TOE) Framework and qualitative comparative analysis method have also been applied to the provincial governments of China. The study suggests the improvement in the level of OD of provincial governments, for strengthening their cooperation among government departments and disciplinary inspection sections. The results show that the Policy Ensuring (PE), Online Platform (OP)’s availability, Technological Embeddedness (TLE), and Open Data Usefulness (ODU) all affect CG drives. Furthermore, a hypothesis has been established that environmental constraints and the pressure of locals can affect the reliability of open data in a positive way.